St. Stephen's Chapel, looking east, Westminster - Billings, R. W. (Robert William); Le Keux, John (Tufts Archival Research Center, 2006)
This illustration is from Charles Knight's "London," Vol. 2. This image was inserted by Edwin C. Bolles and is not found in the original.